Agglomerated Co–Cr/SBA-15 catalysts for hydrogen production through acetic acid steam reforming. (11th June 2020) - Calles, J.A.; Carrero, A.; Vizcaíno, A.J.; Megía, P.J.
Abstract: Hydrogen produced from renewable resources is becoming interesting as an alternative to conventional fossil fuels. Co-based catalysts have been reported for their active role in steam reforming of acetic acid as the main model compound of bio-oil aqueous fraction. In the present work, a series of Co–Cr/SBA-15 extrudates were prepared by varying the binder (bentonite) content and particle size in order to get catalyst particles suitable to be used in a steam reformer at industrial scale. Catalysts were characterized by N2 physisorption, ICP-AES, TEM, SEM, XRD and H2 -TPR. The physicochemical characterization results showed that no remarkable changes occurs after the extruding process of the powdered sample, except for the particle size and mechanical strength. Acetic acid steam reforming tests were done at 600 °C and WHSV = 30.1 h −1 varying the feed flow rate and the catalysts particle size in order to study the influence of internal and external diffusion limitations. Extruded particles with an effective diameter of 1.5 mm and 30 wt% of bentonite get similar conversion and hydrogen selectivity than powder sample. Besides, the agglomerated catalysts are also stable up to 12 h of TOS. Highlights: Acetic acid steam reforming was evaluated using agglomerated Co–Cr/SBA-15 catalysts. Bentonite content enhances mechanical properties. Higher bentonite content leads to more homogeneous particle shape of extrudates. Extrudates get similar conversion and hydrogen selectivity than powder sample.